Overexpression of Tear Inflammatory Cytokines as Additional Finding in Keratoconus Patients and Their First Degree Family Members - Ionescu, Ioana Catalina; Corbu, Catalina Gabriela; Tanase, Cristiana; Ionita, Gabriela; Nicula, Cristina; Coviltir, Valeria; Potop, Vasile; Constantin, Mihaela; Codrici, Elena; Mihai, Simona; Popescu, Ionela Daniela; Enciu, Ana-Maria; et al. (Mediators of Inflammation, 2018)
Keratoconus is a progressive corneal ectasia that may lead to severe visual impairment due to the irregular astigmatism caused by corneal thinning. In addition to its association with atopy, eye rubbing, or genetic component, late reports suggest the involvement of inflammation in the pathogenesis of the disease. Our aim was to determine the concentration of IL-4, IL-6, IL-10, RANTES, IFN gamma, and TNF alpha in the tear film of patients with keratoconus and their first degree family members. We analyzed forty-eight participants in an observational cross-sectional study. The diagnosis of keratoconus had to be confirmed in addition to a minimum of 47 D corneal refractive power by corneal topography readings provided by a Placido-based topography system and analysis of the pattern: irregular astigmatism with an asymmetric “bow-tie.” As for the other groups, the most important diagnosis criteria were a normal topographic pattern with a regular astigmatism. 17 keratoconus patients, 16 relatives, and 15 controls were recruited after clinical assessment as part of the research. The cytokine’s mean values were similar in the keratoconus group and the relatives’ samples but significantly higher compared to the controls. Important differences were found in IL-4 levels between keratoconus patients and relatives and between relatives and controls (mean difference of 302.42, p<0.0016 and 219.16, p<0.033, Tukey’s HSD procedure). In the keratoconus group, using the CORR procedure, we found statistically strong correlations of IL-6 lacrimal concentrations with the disease stage (r=0.56, p<0.01), keratometry (r=0.55, p<0.02), pachymetry (r=−0.64, p<0.048), and corneal hysteresis (r=−0.53, p<0.02). Cytokine overexpression may be relevant for the inflammatory etiology of keratoconus. In conclusion, in the case of some first degree family members, the elevated tear biomarkers may represent a supplementary risk factor.